Surface Analysis of Inhibitor Film Formed by Poly(Vinyl Alcohol) on Stainless Steel in Sodium Chloride Solution - Samide,A. (2010)
The corrosion inhibition of stainless steel in 0.9% NaCl solution in presence of poly(vinyl alcohol) (PVA) is discussed according to electrochemical measurements, such as potentiodynamic polarization and electrochemical impedance spectroscopy (EIS).The morphology of the surface was analyzed using Scanning Electron Microscopy (SEM). The composition of the layer formed on stainless steel surface was estimated using X-ray Photoelectron Spectroscopy (XPS) technique. Electrochemical measurements indicated that the presence of PVA in NaCl solution decreases the corrosion current and increases the polarization resistance. The values of inhibition efficiency obtained from polarization curves and EIS measurements are in good agreement. In absence and in presence of PVA, SEM images showed that the stainless steel surface was covered with a non-uniform layer and a uniform adsorbed film, respectively. XPS analysis indicated that the surface layer consists of PVA containing a small amount of other elements, such as Na and Cl.